Betulinic Acid and Taccalin as Potential Modulators of Granulysin Mediated Keratinocyte Apoptosis in Erythema Multiforme - Kumar, Samritha; Selvam, Suganya Panneer; Krishnasamy, Nitya (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Erythema multiforme (EM) is an immune-mediated mucocutaneous disorder characterized by keratinocyte apoptosis, with granulysin (GNLY) identified as a key cytotoxic mediator. Targeting GNLY may offer a promising strategy for developing more specific and safer therapeutic interventions. Objective: To evaluate the potential of phytochemicals derived from Tacca integrifolia as modulators of GNLY mediated apoptosis using computational approaches. Methods: Protein–protein interaction (PPI) analysis of GNLY was performed using the STRING database to identify its role in apoptotic and immune pathways. Selected phytochemicals—taccalin, betulinic acid, gamma aminobutyric acid (GABA), and guaijaverin—were retrieved and assessed for their interaction with GNLY. Drug likeness and pharmacokinetic properties were evaluated using standard ADMET prediction tools. Results: PPI analysis revealed GNLY as a central hub interacting with key cytotoxic proteins, including perforin and granzymes, highlighting its role in immune-mediated apoptosis. Interaction analysis demonstrated favorable binding affinities ranging from –3.4 to –6.8 kcal/mol, with betulinic acid and taccalin showing the strongest interactions. Drug-likeness and ADMET evaluation identified taccalin, betulinic acid, and GABA as promising candidates with favorable pharmacokinetic profiles, including non-permeability to the blood–brain barrier and low predicted toxicity. Conclusion: Phytochemicals derived from Tacca integrifolia, particularly taccalin, betulinic acid, and GABA, show potential as modulators of GNLY-mediated apoptosis. These findings highlight a novel GNLY-targeted therapeutic approach for erythema multiforme and warrant further validation through molecular dynamics simulations and experimental studies.